POWER RELATIONSHIP MARKETING DALAM BISNIS - Hasan, Ali (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2017)
Understanding the motivations of consumers to engage in relationships with marketers is important for both practitioners and marketing scholars. To develop an effective theory of relationship marketing, it is necessary to underÂ¬stand what motivates consumers to reduce their available market choices and engage in a relational market behavior by patronizing the same marketer in subsequent choice situations. This article draws on established consumer behavior literature to suggest that consumers engage in relational marker behavior due to personal influences, social influences, and institutional influences. Consumers reduce their available choice and engage in relational market behavior because they want to simplify their buying and consuming tasks, simplile information processing, reduce perceimd risky, and maintain convetitive consistency and a state of psychological comfort. The willingness and ability of both consumers and marketers to engage in relational marketing will lead to greater marketing productivity; unless either consumers or marÂ¬keters abuse the mutual interdependence and cooperation. This article examines theoretical contributions to a comprehensive relationship marketing concept. In the modern of marketing sciences, that interaction in networks of relat ionships constitutes both the essence of life itself and the essence of society. Marketing just applying the perspective of its own discipline and not properly considering the context within which marketing operates. The article offers an overview of the contributions to relationship marketing from traditional consumer goods marketing, services marketing, business marketing and base theory for research. Key word : power of relationship marketing, service and goods marketing, and customer profitability.